Estudio de la funcionalidad y morfología cardíaca en ratas adultas expuestas a una deficiencia moderada de zinc durante el crecimiento prenatal y/o postnatal - Juriol, Lorena Vanesa (2016)
The aim of this study was to evaluate whether moderate zinc restriction in rats throughout fetal life and/or post-weaning growth results in cardiac changes that predispose the onset of cardiovascular dysfunction in adult life, and sex-related differences in the adaptation to this nutritional injury.\nFemale Wistar rats received low or control zinc diets from the beginning of pregnancy up to weaning. Afterwards, offspring were fed either a low or control zinc diet until adulthood.\nZinc deficiency during fetal and postnatal life induced an increase in systolic blood pressure levels and a decreased contractility associated to increased apoptosis, inflammation, anti-oxidant enzymes, and a decreased TGF-?1 expression, nitric oxide system and calcium handling in male left ventricles. Adequate zinc intake during post-weaning life did not overcome blood pressure levels but reversed some of the detrimental effects in cardiac morphology and function. Females were less sensitive to this deficiency, exhibiting normal levels of blood pressure and no significant structural or functional heart alterations in adult life.\nThis study strengthens the importance of diet care optimization, not only during prenatal development to prevent programming of cardiovascular diseases, but also during postnatal life to diminish the consequences of an adverse event during fetal life